Evaluating the Effect of EFL College Students’ Intention To Utilize Mobile English Vocabulary in The Learning Process: A TAM Framework - Haidar Farros; Arundati Shinta; Zaid Zaid; Mahbub Pasca Al Bahy (Universitas Hamzanwadi, 2022)
In today's world, it is no longer a surprise that (smart) mobile devices have become the most helpful technological devices to be used for various purposes, one of which is in English education. Therefore, studies on improving language learning, especially vocabulary for learners using mobile device technology, have become commonplace in today's digital era. However, to achieve maximum use, there needs to be an intention from students to accept the English vocabulary technology in the learning process. Therefore, the purpose of this study was to evaluate the integration capability of the Technology Acceptance Model (TAM) to predict and explain EFL college students' intention to utilize mobile English vocabulary learning. This research involves TAM because TAM has been widely applied to study information technology because of its effectiveness in assessing the level of user acceptance. Through a quantitative method using a cross-sectional survey approach involving 456 respondents, this study ultimately found that, after being analyzed using the PLS-SEM analysis technique, the constructs in TAM, including perceived ease of use (β = 0.302, T-Value = 6.587, and P-value = 0.000) and usefulness (β = 0.359, T-Value = 7.501, dan P-value = 0.000), had a positive and significant effect on EFL college students' intention to utilize mobile English vocabulary. Perceived usefulness shows the most dominant effect. However, this study has limitations that need to be considered. And, of course, caution in generalizing is necessary.